2009
DOI: 10.2147/nss.s7040
|View full text |Cite
|
Sign up to set email alerts
|

Normal regional brain iron concentration in restless legs syndrome measured by MRI

Abstract: Using a T 2 * gradient echo magnetic resonance imaging (MRI) sequence, regional T 2 signal intensity (SI) values, a surrogate marker for T 2 values, were determined in 12 regions of interest (substantia nigra, pallidum, caudate head, thalamus, occipital white matter, and frontal white matter bilaterally) and in two reference regions (cerebrospinal fluid and bone) in 12 patients suffering from moderate to severe idiopathic restless legs syndrome (RLS; mean age 58.5 ± 8.7 years) for 12.1 ± 9.1 years and in 12 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Discordant results are also present in the literature and specifically in two studies [84,85]. One study using T2* gradient echo MRI sequences did not find significant differences in regional signal intensity in levels of 12 regions of interest (substantia nigra, pallidum, caudate head, thalamus, occipital WM, and frontal WM bilaterally) [84].…”
Section: Imaging Findings In Rls Patientsmentioning
confidence: 54%
“…Discordant results are also present in the literature and specifically in two studies [84,85]. One study using T2* gradient echo MRI sequences did not find significant differences in regional signal intensity in levels of 12 regions of interest (substantia nigra, pallidum, caudate head, thalamus, occipital WM, and frontal WM bilaterally) [84].…”
Section: Imaging Findings In Rls Patientsmentioning
confidence: 54%
“…Although we did not evaluate the SN pars compacta and pars reticulata separately, this result is consistent with the present findings. Knake et al15 did not find any difference in the iron content between idiopathic RLS patients and controls, while Margariti et al16 found an increase in the iron contents in the subthalamic nucleus and the globus pallidus, but not in the SN of early-onset RLS patients.…”
Section: Discussionmentioning
confidence: 94%
“…Some later studies, however, reported lower SN iron concentrations in late-onset RLS [11, 12], but not in early-onset RLS, either using R2 [15] or R2′[12]. Moreover, there is one study reporting no change in the MRI based iron index (R2* weighted signal intensity) in RLS [16] and another reporting increased iron index (R2) in early-onset RLS without medical treatment [15]. Besides biological variations, small sample sizes, uncertain differential diagnosis of RLS and controls, and possible treatment-induced brain iron changes [17], such discrepancies may be attributed to the different MRI techniques used for measuring tissue iron contents with different sensitivities and methodological limitations [18].…”
Section: Introductionmentioning
confidence: 99%